Adverse Effects of Meditation: Autonomic Nervous System Activation and Individual Nauseous Responses During Samadhi Meditation in the Czech Republic - Kotherová, Silvie (Journal of religion and health, 2024)
Buddhist meditation practices, including Samadhi meditation, which forms the basis for mindfulness practice, are broadly promoted as pathways to wellbeing, but evidence of their adverse effects is emerging. In a single-group observational study with assessments of autonomic system before, during, and after Samadhi meditation, we explore the relationship between post-meditation nausea symptoms and the degree of change in autonomic system activity during meditation as compared to before and after in 57 university students (42 women; mean age = 22.6) without any previous experience in meditation or yoga practices. We hypothesize that nauseous feelings in meditation are connected to a rapid increase of activity in the sympathetic nervous system, as indicated by decreased heart-rate variability (HRV). We additionally explore links between meditation-induced nausea and two markers of parasympathetic activity: increased HRV and vasovagal syncope. Engaging in meditation and increased nausea during meditation were both associated with increased markers of HRV parasympathetic activity, but 12 individuals with markedly higher nausea demonstrated increased HRV markers of sympathetic activity during meditation. Vasovagal syncope was observed but found to be unrelated to nausea levels. Drivers of adverse effects of meditation in some individuals require further investigation.